An Empirical Study on the Determinants of Government Revenue in Nepal - Bhoosal, Yam Lal; Byanjankar, Rohan (NRB Economic Review, 2022)
This paper aims to examine the determinants of government revenue in Nepal. The macroeconomic variables, namely, GDP per capita, imports, consumer price index, exchange rate, and foreign aid from 1975 to 2021 have been included to assess their effect on government revenue. We have performed descriptive and econometric analyses. Government revenue increased by about 15 percent on average from 1976 to 2021 and the revenue-to-GDP ratio stood at around 22 percent in 2021. The empirical results reveal that GDP per capita and imports are the major determinants of government revenue in the short run. Likewise, GDP per capita, imports, and exchange rate are the major determinants of government revenue in the long-run. The error correction term suggests that the short-run disequilibrium in the system takes about 3 years to converge to equilibrium.